FABP4-Cre Mediated Expression of Constitutively Active ChREBP Protects Against Obesity, Fatty Liver, and Insulin Resistance - Nuotio-Antar, Alli M. (Endocrinology, 2015)
Carbohydrate response element binding protein (ChREBP) regulates cellular glucose and lipid homeostasis. Although ChREBP is highly expressed in many key metabolic tissues, the role of ChREBP in most of those tissues and the consequent effects on whole-body glucose and lipid metabolism are not well understood. Therefore, we generated a transgenic mouse that overexpresses a constitutively active ChREBP isoform under the control of the fatty acid binding protein 4-Cre-driven promoter (FaChOX). Weight gain was blunted in male, but not female, FaChOX mice when placed on either a normal chow diet or an obesogenic Western diet. Respiratory exchange ratios were increased in Western diet-fed FaChOX mice, indicating a shift in whole-body substrate use favoring carbohydrate metabolism. Western diet-fed FaChOX mice showed improved insulin sensitivity and glucose tolerance in comparison with controls. Hepatic triglyceride content was reduced in Western diet-fed FaChOX mice in comparison with controls, suggesting protection from fatty liver. Epididymal adipose tissue exhibited differential expression of genes involved in differentiation, browning, metabolism, lipid homeostasis, and inflammation between Western diet-fed FaChOX mice and controls. Our findings support a role for ChREBP in modulating adipocyte differentiation and adipose tissue metabolism and inflammation as well as consequent risks for obesity and insulin resistance.